2010
DOI: 10.1590/s1516-89132010000500010
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and evaluation of glipizide floating-bioadhesive tablets

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…However, the effect of the polymer Badam gum was more pronounced than HPMC K4 M on bioadhesion strength since Badam gum has significant sticking property these findings are in agreement with previously reported results by Meka, et al, [23] who found the Badam gum has remarkable swelling and sticking character in gastric pH. [23][24][25][26][27][28][29][30][31][32][33] This developed floating-bioadhesive combination formulation would overcome the drawback of floating and bioadhesive individual system and improving the therapeutic effect of the drug involved.…”
Section: Bioadhesive Strengthsupporting
confidence: 90%
See 1 more Smart Citation
“…However, the effect of the polymer Badam gum was more pronounced than HPMC K4 M on bioadhesion strength since Badam gum has significant sticking property these findings are in agreement with previously reported results by Meka, et al, [23] who found the Badam gum has remarkable swelling and sticking character in gastric pH. [23][24][25][26][27][28][29][30][31][32][33] This developed floating-bioadhesive combination formulation would overcome the drawback of floating and bioadhesive individual system and improving the therapeutic effect of the drug involved.…”
Section: Bioadhesive Strengthsupporting
confidence: 90%
“…From this mucoadhesive strength, the force of adhesion, i.e., the force required for separating the tablet from the tissue surface was calculated using the following formula. [24][25][26][27][28][29][30][31] Force of adhesion N = Bioadhesive strength 9.81…”
Section: Si Studymentioning
confidence: 99%
“…HPMC, pectin, carbopol, sodium bicarbonate and citric acid were weighed and passed through sieve number #40 individually. Powder mixing was carried out in a clean mortar and mixed thoroughly using a pestle [9]. Above powdered mixture was divided into two halves.…”
Section: Preparation Of Coat Layermentioning
confidence: 99%
“…The solubility, dissolution, and eventually the bioavailability of GLZ can be improved by different techniques such as development of liquisolid tablets by using poly­(ethylene glycol)-400 (PEG-400) as a liquid vehicle, polymeric microparticles, , polymeric nanoparticles, co-solvent solubilization approach, complexation of GLZ with α and β-cyclodextrins, solid self-nanoemulsification, microemulsion technology, , preparation of osmotically controlled oral drug-delivery system, solid dispersion, nanosuspension, microwave-generated bionanocomposites, transdermal drug-delivery system, floating bioadhesive drug-delivery system, and microcrystallization . The solubility data of GLZ in various neat solvents (NS) are scarce in research database.…”
Section: Introductionmentioning
confidence: 99%